2019
DOI: 10.3390/microorganisms7110570
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophages as Potential Tools for Detection and Control of Salmonella spp. in Food Systems

Abstract: The global problem of antibiotic resistance in bacteria is quickly developing in most antibiotics used in hospitals and livestock. Recently, the infections with multi-drug resistant (MDR) bacteria become a major cause of death worldwide. Current antibiotics are not very effective in treating MDR Salmonella infections, which have become a public health threat. Therefore, novel approaches are needed to rapidly detect and effectively control antibiotic-resistant pathogens. Bacteriophages (phages) have seen renewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 156 publications
(159 reference statements)
1
25
0
Order By: Relevance
“…These results are in line with other researchers, who stated that the presence of phages in the farm environment would suggest the bacterial strain has been present at some point in the recent past [12,38]. In addition, this fact could be used for the indirect detection of pathogens based on their specificity towards bacteria [32,39]. In this line, phages against S. Virchow, S. Hadar and S. Ohio were observed to be more prevalent in broilers than in layers.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are in line with other researchers, who stated that the presence of phages in the farm environment would suggest the bacterial strain has been present at some point in the recent past [12,38]. In addition, this fact could be used for the indirect detection of pathogens based on their specificity towards bacteria [32,39]. In this line, phages against S. Virchow, S. Hadar and S. Ohio were observed to be more prevalent in broilers than in layers.…”
Section: Discussionsupporting
confidence: 91%
“…Phage patterns obtained against different Salmonella serovars per farm in this study indicated that the environment of animal farms, especially poultry operations, could represent an important source of Salmonella phages against several serovars [30,31]. In this sense, the phages obtained could be effective to combat these antibiotic-resistant strains, with the aim of controlling Salmonella AMR and its spread to the food chain [32].…”
Section: Discussionmentioning
confidence: 68%
“…Current methods to treat acute Salmonella gastroenteritis are dependent upon supportive care and antibiotic regimens. The overzealous application of antibiotics, especially in the farm setting, has led to the selection of antimicrobial-resistant strains [17,18], which have contaminated food and water systems, and pose a worldwide threat. Under these circumstances, the measures employed to control Salmonella must not lead antimicrobial resistance, which has garnered interest in biological controls.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonellosis is one of the most common foodborne diseases, and its control still remains a challenge worldwide (Wei et al, 2019 ). Probiotics have long been used to control Salmonella enteritidis infection (Chambers and Gong, 2011 ; Forkus et al, 2017 ; Gut et al, 2018 ; Lai and Huang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%